Men as partners in maternal health: an analysis of male awareness and attitude - Narang, Harkiran; Singhal, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Men remain an authority in all the aspects of reproductive health from policy making to its implementation at grass root level. Present study was conducted to determine the awareness and participation of men in maternal health care and to assess their attitude towards their partners. Methods: We conducted a study in which 232 husbands accompanying their wives for delivery in teaching hospital of a metropolitan city were interviewed using a questionnaire. The questions were framed to assess their attitude, knowledge and participation in pregnancy care and maternal health Results: 61% of participants had accompanied their wives to the antenatal clinics at one or the other time. However despite of coming to hospital 60.1% were not aware of the components of antenatal care like number of tetanus immunizations or requirements of increased diet during pregnancy. 44% of the men did not approve of their wives working outside home. 30% of the men admitted to have physically abused their partner on single or multiple occasions. 31% of the pregnancies were unplanned. 75.7% of the men thought that ideal family size comprises of two children. Only 36.2% of the men knew that male sterilization was safer than female sterilization. Conclusion: Men in India have been marginalized in the dispense of antenatal and reproductive health care with policies emphasizing on the services and infrastructure more than involving men as responsible partners. Changes in men's and women's knowledge, attitudes and behavior are necessary conditions required in achieving the millennium development goals.